University of Nairobi Students’ Locus of Control - Tuntufye Selemani Mwamwendaand, Priscilla Wanjiru Kariuki, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a recent definition, Joeison (2017) expresses as follows: “Locus of control is an individual’s belief system regarding the causes of his/her experiences and factors to which the person attributes success or failure”. As a person with internal locus attributes his/her success to hi/her own effort and ability. Such a person is more motivated and likely to successfully acquire new knowledge.